A~holistic approach to model electricity loads in cities; Ein ganzheitlicher Ansatz zur Modellierung des Stromverbrauchs in Städten - S. Köhler; M. Betz; E. Duminil; U. Eicker; B. Schröter (Sustainability Management Forum, 2021)
Time-resolved, occupancy-dependent electricity load profiles at building level for city quarters or entire cities are important for planning authorities, project developers, utilities or other stakeholders in order to develop energy saving strategies and meet climate targets. Firstly, this information enables a~more accurate modelling of renewable energy systems. Secondly, aspects like sector coupling, storage decisions and the impact of technologies such as electric vehicles or heat pumps on the grid can be considered. Thirdly, it allows a~more detailed economic analysis. This paper contains the newly added features to the simulation environment SimStadt, which is used for strategic modelling of sustainable urban or regional areas with a~spatial resolution at the building level. SimStadt interlinks 3D CityGML models with parameters for buildings physics to simulate energy demands and renewable energy potential. It was enhanced by the development of an electricity load profile generator with variable resolution and the addition of an hourly resolved PV potential analysis including a~variable economic analysis. This enables e.g. the evaluation of photovoltaic potential with the associated investment, operating and levelized costs over the lifetime of hundreds of individual buildings in parallel. Together with additional electric building demand from heat pumps, electric vehicles or load shifting options through the use of battery storage, it will be possible to assess and compare the feasibility, benefits and economic viability of energy/electricity-related urban renewal measures in even greater detail and with a~holistic perspective. The simulation platform enables the development of granular sustainable urban (sub)strategies and energy concepts through a~holistic, time-resolved, building-specific approach to support transformation of the building stock to a~sustainable, low-carbon one.
Keywords: 650; Energy Simulation Tool; Urban Modelling Environment; Urban Energy Concepts; Feasibility and Efficiency of Renewable Energies; Neighborhood Strategies; Stepless Scalability